Evaluation of handgrip strength as a predictor of sarcopenia in patients with HCV-related cirrhosis - Mohammed Magdy Salama; Essam Mohammed Bayoumi; Moataz Mohammed Sayed; Samia Ahmed Abdul-Rahman; Shereen Abo Baker Saleh; Ayman Samwel Zaky; Ghada Abdelrahman Mohamed (Egyptian Liver Journal, 2023)
Abstract Background Sarcopenia, characterised by a loss of muscle strength, quantity/quality, and physical performance, is associated with increased mortality and poor clinical outcomes in patients with liver cirrhosis. The use of the currently accepted methods for estimating muscle mass, such as computed tomography, dual-energy X-ray absorptiometry, and bioelectrical impedance analysis, in routine clinical practice is restricted because of limited availability, radiation exposure, time consumption, or high cost. Therefore, an alternative, simple, safe, reproducible, and financially accessible method for the routine assessment of sarcopenia is needed. Hence, we aim to assess the utility of handgrip strength (HGS) in diagnosing sarcopenia in patients with HCV-related cirrhosis compared to appendicular skeletal muscle index assessed by dual-energy X-ray absorptiometry (DEXA-ASMI). A total of 64 participants older than 18 years were consecutively recruited. The subjects were divided into the following groups: Control group included 32 healthy control subjects, and the HCV-related liver cirrhosis group included 32 patients who were subdivided equally into two subgroups (Child A and Child C) with 16 patients each. All participants were subjected to dominant hand dynamometer and DEXA scan. Results The prevalence of sarcopenia was significantly higher in the cirrhosis group than in the control group (7.75 ± 1.35 vs. 8.29 ± 1.25 kg/m2, P < 0.001), with increasing prevalence in the Child C class group (P < 0.001). HGS was significantly lower in the Child C group compared to other groups (P < 0.001). Regarding the differentiation of sarcopenic patients, defining HGS using a cutoff of ≤ 28.6 kg has an AUC of 0.879, sensitivity of 100%, specificity of 66.7%, PPV of 61.1%, and NPV of 100% (95% CI = 0.715 to 0.967; P < 0.0001). Conclusion Given the low cost, reproducibility, and safety of handgrip strength dynamometry, this is a promising method for both the diagnosis of sarcopenia as well as serial monitoring of muscle function in patients with HCV-related cirrhosis.